Changes in retinal nerve fiber layer thickness after Pars Plana Vitrectomy with internal limiting membrane peeling in patients with a macular hole or epiretinal membrane: literature review - Saraiva, Carina (2023)
Introduction – Pars Plana Vitrectomy (PPV) is a vitreoretinal surgical technique that allows access to the posterior eye segment, enabling its treatment. It is, currently, the gold standard treatment for pathologies such as epiretinal membrane (ERM) and macular hole (MH), and is usually accompanied by the peeling of the inner limiting membrane (ILM), a boundary structure between the retina and the vitreous, eliminating the tangential traction involved in the genesis of these pathologies. As the retinal nerve fiber layer (RNFL) is an essential structure for the conduction of nervous impulses and is adjacent to the ILM, we intend to carry out a review of the literature that addresses the changes in the RNFL after PPV with ILM peeling in patients with MH or ERM, found in optical coherence tomography spectral domain (SD-OCT). Aim of the study – To carry out a review of the literature on changes in RNFL thickness and architecture in patients undergoing PPV with ILM peeling, in the treatment of MH and/or ERM, and how they can compromise its integrity, by reviewing articles that include population sample monitoring through SD-OCT. Methods – This study is a literature review. The search was carried out in PubMed, Scopus, and Web of Science databases. The review and selection of the articles was carried out, following the PRISMA methodology, between October 2020 and July 2021, using two tools: Health Evidence Quality Assessment tool – Review Articles and CASP (Critical Appraisal Skills Program), with a total of sixteen articles selected. Results – Five out of the 16 selected articles showed a dissociation of RNFL after PPV with peeling ILM for the treatment of MH or EM, and 11 of the 16 articles showed that there was a decrease in RNFL thickness after the surgical procedure. Conclusions – The results show that there is a significant rate of cases of dissociation of nerve fibers and/or decreased RNFL thickness after edema in the immediate postoperative period. Some studies point to a predominance of the temporal sector of the retina, mostly without harming of the macular region.